2010
DOI: 10.1093/eurheartj/ehq277
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on myocardial revascularization: The Task Force on Myocardial Revascularization of the European Society of Cardiology (ESC) and the European Association for Cardio-Thoracic Surgery (EACTS)

Abstract: Disclaimer. The ESC Guidelines represent the views of the ESC and were arrived at after careful consideration of the available evidence at the time they were written. Health professionals are encouraged to take them fully into account when exercising their clinical judgement. The guidelines do not, however, override the individual responsibility of health professionals to make appropriate decisions in the circumstances of the individual patients, in consultation with that patient, and where appropriate and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
734
2
110

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,326 publications
(862 citation statements)
references
References 277 publications
8
734
2
110
Order By: Relevance
“…Here, nearly one‐third of the patients with suspected CAD and non‐contributive electrocardiography and troponin had FFR <0.8. Albeit the existence of an FFR “gray zone” from 0.75 to 0.80 was previously reported for decision‐making,35, 36, 37 where the chosen FFR threshold value of 0.80 was clearly associated with the presence of spare A 2A R displaying a high K D /EC 50 ratio. Importantly, this test may help distinguish patients who require hospitalization in a cardiac department or monitoring only.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Here, nearly one‐third of the patients with suspected CAD and non‐contributive electrocardiography and troponin had FFR <0.8. Albeit the existence of an FFR “gray zone” from 0.75 to 0.80 was previously reported for decision‐making,35, 36, 37 where the chosen FFR threshold value of 0.80 was clearly associated with the presence of spare A 2A R displaying a high K D /EC 50 ratio. Importantly, this test may help distinguish patients who require hospitalization in a cardiac department or monitoring only.…”
Section: Discussionmentioning
confidence: 76%
“…Only ACS statut constitutes an issue for FFR measurement (duration and intensity of ischemia, embolization spasm) while the clinical impact of these changes is minimal. Earlier data comparing FFR measurements at the acute phase or a week later would have led the same clinical decision about the need for revascularization 35. At least, our study included patients on average 4 days after the index period (delay for performing non‐invasive tests), which suggested a majority of stabilized “unstable syndromes” while we have excluded high‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, cumulative evidence suggests that angiographically determined anatomical stenosis severity often underestimates or overestimates the functional significance of lesions 5, 6, 7. Fractional flow reserve (FFR) is currently the standard for decision‐making regarding revascularization in the catheter laboratory and has become part of the clinical guidelines for the assessment of the physiological significance of epicardial coronary stenosis based on sound concepts and randomized clinical trials 8, 9, 10, 11. However, FFR evaluation is still underutilized; instead, coronary angiography is widely used as a gatekeeper for decision‐making of revascularization even in large clinical trials 2, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional flow reserve (FFR) is the standard in decision making for revascularization in the catheter laboratory and has become a part of the clinical guidelines for assessing the physiological significance of epicardial coronary stenosis based on a sound concept and randomized clinical trials 1, 2, 3, 4. A recent study also suggested that FFR measured after percutaneous coronary intervention (PCI) has prognostic value, with an inverse relationship to subsequent clinical events 5.…”
Section: Introductionmentioning
confidence: 99%